First report of Porphyromonas pogonae infection in a bat (Nyctalus noctula): implications for wildlife health and zoonotic potential - Dondini, Gianna; Ratti, Gabriele; Consolo, Marcello; Giacolini, Clarissa; Vergari, Simone (Journal of Wildlife and Conservation Medicine, 2026)
Porphyromonas pogonae is an anaerobic, Gram-negative coccobacillus originally isolated from the oral cavity of bearded dragons (Pogona vitticeps) and occasionally associated with opportunistic infections in humans. Here, we report the first documented case of P. pogonae infection in a mammalian species, the common noctule (Nyctalus noctula). In 2024, a male bat admitted to a wildlife rescue center in northern Italy for a fractured wing developed a persistent wrist abscess. Bacteriological examination revealed a pure culture of P. pogonae, identified by MALDI-TOF MS. Antimicrobial susceptibility testing showed susceptibility to amoxicillin/clavulanic acid, clindamycin, and metronidazole, and resistance to penicillin and ampicillin. Following targeted antimicrobial therapy, complete clinical recovery was achieved. This report expands the known host range of P. pogonae and highlights the importance of microbiological diagnostics in wildlife medicine. The detection of this bacterium in a chiropteran host suggests potential ecological and zoonotic implications that warrant further investigation.